NVTIA™ 5-HTP–L-Theanine–GABA Sleep Rhythm Support System: Ratio Optimization, Gastrointestinal Tolerability, and Evidence from Human Studies and Preclinical Evaluation - Yassine, Jabar; Semenza, Gregg L.; Collins, Lily (International Journal of Agriculture and Food Sciences Research, 2026)
Background: Nutritional sleep-support strategies often underperform because they address only one pathway or do not balance efficacy with tolerability. We examined an NVTIA™ 5-HTP–L-theanine–GABA ternary system and aligned its disclosed formulation and mouse data with current published human evidence on the same three axes. Methods: We summarized the disclosed composition window, excipient module, process parameters, and preclinical sleep-evaluation results, and screened recent peer-reviewed human trials and evidence syntheses available through March 2026. Results: Published human evidence supports biological plausibility and modest clinical benefit for the individual components. A 12-week randomized controlled trial in older adults found that 100 mg/day 5-HTP improved certain sleep-quality components, particularly in poor sleepers. A 2025 meta-analysis of L-theanine trials reported significant improvements in subjective sleep-onset latency, daytime dysfunction, and overall subjective sleep quality. A 4-week double-blind trial of 300 mg/day oral GABA showed reduced sleep latency and improved sleep efficacy, although systematic-review evidence for oral GABA remains limited and heterogeneous. Against this clinical background, the disclosed ternary formulations showed dose-responsive preclinical performance. Conclusions: The NVTIA™ platform is best interpreted as a coordinated formulation-engineering system in which precursor support, relaxation support, inhibitory-neurotransmission support, gastrointestinal-tolerability excipients, and process control are aligned. These results justify further controlled human validation of optimized ternary ratios.